EP.WE.805From bench to bedside; A rationale for Immunotherapy in the adjuvant setting for Oesophageal cancer. (28th October 2021) - Donlon, Noel; Davern, Maria; Sheppard, Andrew; Reynolds, John; Lysaght, Joanne
Abstract: Background: Immunotherapy is being intensively investigated for its utilisation in the curative setting as a single agent and in the multimodal setting, however, the most appropriate time to incorporate ICIs remains unknown. Our study profiles systemic anti-tumour immunity perioperatively to provide a rationale for adjuvant immunotherapy. Methods: Systemic immunity was immunophenotyped pre and post-oesophagectomy on days 0, 1, 3, 7 and week 6 by flow cytometry (n = 14). The frequency of circulating lymphocytes, T cells, cytotoxic and helper T lymphocytes was profiled longitudinally including the proportion of T cell subsets in circulation. This study also profiled immune checkpoint expression on circulating T cells including: PD-1, CTLA-4, TIGIT, TIM-3, LAG-3, PD-L1 and PD-L2. Markers of immunogenicity (calreticulin, HMGB1 and MIC-A/B) were also assessed. Results: The frequency of circulating CD27 + T cells increases sequentially in the immediate post-operative period peaking on day 7 in OAC patients. (p < 0.01) There is a sequential decrease in the percentage of effector memory and central memory T cells in circulation and an increase in the percentage of naïve T cells in peripheral circulation of OAC patients in the immediate post-operative period. The expression of CTLA-4 on the surface of circulating CD4 + T cells decreases 6 weeks post-operatively in OAC patients. Conclusions: We observed increased T cell activation and immune checkpoints immediately post-surgery with returns to baseline by week 6. These results suggest that immune checkpoint inhibitors such as anti-PD-1 may be beneficial immediately post-surgery to maintain T cell activation and prevent exhaustion of this increased population of activated T cells observed immediately post-surgery.